Simulation and analysis performance of 4-QAM and 8-PSK by using Reed Solomon codes in WCDMA environment / Siti Suliza Shuib - Shuib, Siti Suliza (2009)
This project illustrates the simulation and performance of 4-QAM and 8-PSK in WCDMA. This model consists of transmission channel, transmitter and receiver. This simulation is dealing with two channels. Channel one is using 4-QAM and channel two is using 8-PSK. Reed Solomon codes is use to encode and decode the signal of the two channels before modulation and after demodulation process. The main objective of this project is to compare and identify which channel is better by analyzing the performance of both channels in term of bit error rate (BER). This project is simulated by using Matlab Version 7.6.